Karakterisasi berbagai Jenis Bahan Lapisan Kedap, Ketebalan dan Nisbah Bentonit dengan Pasir: Konsep Dasar Pengelolaan Lahan Pasir Pantai - Saparso, Saparso; Tohari, Tohari; Shiddieq, Dja’far; Setiadi, Bambang (UNIVERSITY OF LAMPUNG, 2009)
Characterization of Various Kinds, Thickness and Bentonite Sand Ratio as Hardplain Materials: a Basic Concept for Coastal Sandy Land Management (Saparso, Tohari, D. Shiddieq, and B. Setiadi): Coastal sandy land developmentÂ facesÂ the sand characteristics, the lower holding water capacity and the larger nutrient leaching due to heavier rainfall in the tropics, soil porosityÂ and without soil layering so it need alternative technologyÂ forÂ more efficientÂ harvesting water resources inÂ supportingÂ the crop growing. TheÂ laboratory research studied the characteristic of various kind, thickness and ratio of hardplain material was carried out at Laboratory of Agronomy of UNSOED,Â Soil Mechanic of GMU.Â the SEM and X-RD ofÂ Lemigas Jakarta. Permeability determination by Falling Head which is appropriate measurmentÂ was not significantly different with ELE28-290 permeameter. Permeability of Kokap clay soil andÂ Nanggulan bentonite were larger than theÂ rainfall intensity in coastal sandy land.Â The Sentolo Vertisol content 68% calcium smectite had permeability 3,7 mm.day-1.Â Bentonite permeability were not significantly different due to more than 80% clay mineral composition. Therefore the permeability of natrium bentonite like asÂ BPIB andÂ BLUB namelyÂ 1.4 x 10-2 and 10-2Â mm day-1 were lower than the calcium bentonite like as RMBL and BLBKÂ permeability namelyÂ 4.3 x 10-2Â andÂ 2.43 x 10-2 mm day-1. Permeability of 0.5 cm thickness bentonite was notÂ significantly different than 1.0 dan 1.5 cm thickness and those had very low permeability. Bentonite sand mixture 15 and 20 percent produced bentonite sand agregateÂ thatÂ hadÂ mesopores by which allowing the drainage and available soil water so that those had water permeability 13.7 danÂ 10.3 mm day-1 respectively.Â The mixture 30-100%Â had not significantly different permeability namely 7.3 x 10-2Â up to 1.4 10-2 mm day-1. The combination of tickness and the low ratio ofÂ bentonite sand mixutre need to be determined to produce favourable environment in supportingÂ the plant growth.